2022
DOI: 10.1155/2022/7585457
|View full text |Cite
|
Sign up to set email alerts
|

Light Weighted CNN Model to Detect DDoS Attack over Distributed Scenario

Abstract: The minimal-degree distributed denial-of-service attack takes advantage of flaws in the adaptive mechanisms of network protocols, which could have a big impact on network service quality. It is very hard to find, has a low attack rate, and comes at a set time. Detection methods that have been used before have problems because they only use one type of detection and are not very good at identifying the object. In the end, a way to detect many sorts of minimal DDoS assaults that use deep hybrid learning is sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Users face concerns regarding the credibility and security of their data when storing and transmitting it to the CSP. Entrusting data to a third party introduces an additional layer of risk [54].…”
Section: Architecture-based Defensementioning
confidence: 99%
“…Users face concerns regarding the credibility and security of their data when storing and transmitting it to the CSP. Entrusting data to a third party introduces an additional layer of risk [54].…”
Section: Architecture-based Defensementioning
confidence: 99%
“…In the first category, risks pertain to accountability, data ownership, service credibility, and data integration. Users face concerns regarding the credibility and security of t Entrusting data to a third party introduces an additional layer of risk [54].…”
Section: Architecture-based Defensementioning
confidence: 99%
“…In 2022, Kumar et al 23 suggested a light weighted convolutional neural network (CNN) method for detecting DDoS attacks. This method was utilized for DDoS AD at the gateway so that numerous attacks detected at a similar time.…”
Section: Related Workmentioning
confidence: 99%